2000
DOI: 10.3168/jds.s0022-0302(00)74962-9
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Altering the Ratio of Dietary Protein to Energy on Growth, Feed Efficiency, and Mammary Developmentin Rapidly Growing Prepubertal Heifers

Abstract: This study was conducted to evaluate the effects of increasing the ratio of dietary protein to energy above National Research Council recommendations on average daily gain, feed efficiency, structural growth, and indirect measurements of mammary growth. Forty-five Holstein heifers were randomly assigned to either a low, medium, or high ratio of dietary crude protein (CP) to metabolizable energy of 46:1, 54:1, and 61:1 g/Mcal, respectively. The ratio of dietary protein to energy was altered by adjusting the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 21 publications
7
34
1
1
Order By: Relevance
“…It could correct the negative effects of pre-pubertal feeding management and heifers might have better results during first lactation than those fed according to recommendations (Park et al, 1989;Lammers and Heinrichs, 2000). Experiments showed that compensatory growth might have a direct effect on the mammary development of dairy heifers and consequently on milk production (Choi et al, 1997;Ford and Park, 2001).…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…It could correct the negative effects of pre-pubertal feeding management and heifers might have better results during first lactation than those fed according to recommendations (Park et al, 1989;Lammers and Heinrichs, 2000). Experiments showed that compensatory growth might have a direct effect on the mammary development of dairy heifers and consequently on milk production (Choi et al, 1997;Ford and Park, 2001).…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…A shortage of rumendegradable feed protein (RDP) has been shown to reduce microbial digestion of carbohydrates (Griswold et al, 2003;Klevesahl et al, 2003), reduce synthesis of microbial protein (Martín-Orue et al, 2000;Griswold et al, 2003), decrease feed intake (Wheeler et al, 2002) and decrease weight gain of growing cattle (Zinn et al, 1994 and. A shortage of absorbed AA by cattle, either because of decreased synthesis of microbial protein or less than required intakes of rumen-undegraded protein (RUP), decreases weight gain of growing cattle (Lammers and Heinrichs, 2000). Even though individual studies have examined the influence of protein supplementation on the intake and performance of growing cattle, limitations in the number of observations and basal diet composition do not allow for definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Este fato pode ser particularmente importante quando se utiliza polpa cítrica na alimentação de animais em crescimento. Lammers & Heinrichs (2000) verificaram, em novilhas, estreita correlação entre a relação proteína:energia das dietas e a redução na produção de leite ao longo da vida produtiva do animal quando submetido a elevadas taxas de crescimento. Segundo o NRC (2001), o requerimento de proteína depende principalmente do peso corporal do animal, do ganho de peso diário e da digestibilidade da proteína da dieta, sendo que a relação proteína:energia requerida pelos animais pode ser maior em novilhas submetidas a maiores taxas de crescimento.…”
Section: Introductionunclassified